The rapid in vivo evolution of Pseudomonas aeruginosa in ventilator-associated pneumonia patients leads to attenuated virulence - Wang, Ke (2019)
Pseudomonas aeruginosa is an opportunistic pathogen that causes severe airway infections in humans. These infections are usually difficult to treat and associated with high mortality rates. While colonizing the human airways, P. aeruginosa could accumulate genetic mutations that often lead to its better adaptability to the host environment. Understanding these evolutionary traits may provide important clues for the development of effective therapies to treat P. aeruginosa infections. In this study, 25 P. aeruginosa isolates were longitudinally sampled from the airways of four ventilator-associated pneumonia (VAP) patients. Pacbio and Illumina sequencing were used to analyse the in vivo evolutionary trajectories of these isolates. Our analysis showed that positive selection dominantly shaped P. aeruginosa genomes during VAP infections and led to three convergent evolution events, including loss-of-function mutations of lasR and mpl, and a pyoverdine-deficient phenotype. Specifically, lasR encodes one of the major transcriptional regulators in quorum sensing, whereas mpl encodes an enzyme responsible for recycling cell wall peptidoglycan. We also found that P. aeruginosa isolated at late stages of VAP infections produce less elastase and are less virulent in vivo than their earlier isolated counterparts, suggesting the short-term in vivo evolution of P. aeruginosa leads to attenuated virulence.